Swine lake - Marshall, James, 1942-1992 (Harper Collins Publishers, 1999)
A hungry wolf attends a performance of Swine Lake, performed by the Boarshoi Ballet, intending to eat the performers, but he is so entranced by the story unfolding on the stage that he forgets about his meal.